2005
DOI: 10.2135/cropsci2004.0651
|View full text |Cite
|
Sign up to set email alerts
|

The Maize lpa241 Mutation Causes a Remarkable Variability of Expression and Some Pleiotropic Effects

Abstract: Sharpley et al., 1994). These lpa mutants produced seeds in which the chemistry of seed P, but not the total Phytic acid is a nearly ubiquitous component of plant seeds, supplyamount of P, was greatly altered (Raboy and Gerbasi, ing both phosphate (P) and cations during germination. However, during digestion, the phytic acid form of P is not bioavailable for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
69
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 37 publications
11
69
0
Order By: Relevance
“…As independently found for both lpa1-1 and lpa1-241 alleles, mips1S gene expression was reduced in developing seeds (Pilu et al, 2003;Shukla et al, 2004), but in both alleles no molecular lesions in the gene coding region were found (Shukla et al, 2004;Pilu et al, 2005).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…As independently found for both lpa1-1 and lpa1-241 alleles, mips1S gene expression was reduced in developing seeds (Pilu et al, 2003;Shukla et al, 2004), but in both alleles no molecular lesions in the gene coding region were found (Shukla et al, 2004;Pilu et al, 2005).…”
Section: Introductionsupporting
confidence: 70%
“…Although biochemical, mapping and gene expression data suggest the mips1s gene as a candidate for lpa1 mutation in maize (Raboy et al, 2000;Pilu et al, 2003;Shukla et al, 2004;Pilu et al, 2005), recent transposon mutagenesis experiments found that a novel gene designated ZmMRP4 (accession number EF86878), coding a multidrug resistance-associated-protein (MRP) mapping near the mips1s sequence, is the actual responsible gene for lpa1 mutation (Shi et al, 2007). MRP proteins represent a subfamily of ATP-binding cassette transmembrane transporters widespread in all eukaryotes, which in plants are involved in several functions, such as xenobiotic detoxification, organic ions transport, oxidative stress tolerance (Swarbreck et al, 2003) and even transpiration control (Klein et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Low-phytate maize mutants 9 can improve iron bioavailability, 10,11 but have low yields and other negative effects. 12,13 Although natural variability in maize iron bioavailability 14 may provide a path to breeding improved varieties, transgenic biofortification could provide another route. Grains have been engineered for improved iron in a variety of ways.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similarly, antisense transgenic lines of MIPS genes in Solanum tuberosum plants showed altered plant morphology (Keller et al 1998). All low phytic acid (lpa) mutants have been shown to be associated with negative effects in terms of seed physiology and plant performance, such as compromised germination and emergence, stress tolerance, and seed filling (Meis et al 2003;Pilu et al 2005;Bregitzer and Raboy 2006;Guttieri et al 2006). More recently, Campion et al (2009) isolated a P. vulgaris lpa mutant line (lpa-280-10) obtained by the chemical mutagenesis (ethyl methanesulfonate) of a lectine-free bean line showing reduced phytic acid, raffinosaccharides and iron cations in the seed compared with the wild type.…”
Section: Introductionmentioning
confidence: 99%